Thymoquinone protects end organs from abdominal aorta ischemia/reperfusion injury in a rat model - Aydin,Mehmet Salih (2015)
Introduction: Previous studies have demonstrated that thymoquinone has protective effects against ischemia reperfusion injury to various organs like lungs, kidneys and liver in different experimental models. Objective: We aimed to determine whether thymoquinone has favorable effects on lung, renal, heart tissues and oxidative stress in abdominal aorta ischemia-reperfusion injury. Methods: Thirty rats were divided into three groups as sham (n=10), control (n=10) and thymoquinone (TQ) treatment group (n=10). Control and TQ-treatment groups underwent abdominal aorta ischemia for 45 minutes followed by a 120-min period of reperfusion. In the TQ-treatment group, thymoquinone was given 5 minutes. before reperfusion at a dose of 20 mg/kg via an intraperitoneal route. Total antioxidant capacity, total oxidative status (TOS), and oxidative stress index (OSI) in blood serum were measured and lung, kidney, and heart tissue histopathology were evaluated with light microscopy. Results: Total oxidative status and oxidative stress index activity in blood samples were statistically higher in the control group compared to the sham and TQ-treatment groups (P<0.001 for TOS and OSI). Control group injury scores were statistically higher compared to sham and TQ-treatment groups (P<0.001 for all comparisons). Conclusion: Thymoquinone administered intraperitoneally was effective in reducing oxidative stress and histopathologic injury in an acute abdominal aorta ischemia-reperfusion rat model.